PENGARUH KESEJAHTERAAN TERHADAP MOTIVASI KERJA KARYAWAN PADA PT. BERDIKARI KARUNIA ABADI - Sebayang, Immanuel Edy Suranta; Nurhaida, T. (Jurnal Manajemen dan Bisnis, 2022)
PT. Berdikari Karunia Abadi is a consulting and contractor service company that implements welfare programs to increase employee motivation in running its business. The welfare program includes the economy, facilities, and services. This type of research is descriptive qualitative using multiple linear regression analysis which is processed with the help of the SPSS application program. Population 376 employees; sampling by Quota Sampling, the number of samples is 79 respondents. The conclusions of this study: (1) there is a positive but not significant effect of the welfare program which is facility on employees' work motivation as indicated by the value of 2 0.046, t value 0.041, and sig. 0.653. (2) there is a positive but not significant effect of economic welfare programs on employee work motivation as indicated by the value of 1 0.083, t value 0.082 and sig. 0.443. (3) there is a positive influence of economic welfare programs, facility welfare programs, and service welfare programs together on employee work motivation as indicated by the F value of 10,231, the value of sig. 0.000 and the value of R2 is 0.296. This means that 29.6% of employee morale is influenced by economic welfare programs, facilities welfare programs, and service welfare programs, while 71.0% is influenced by other factors not examined in this study. (4) there is a positive influence of service-based welfare programs on employee work motivation as indicated by the value of 3 0.480, t value 0.450 and sig. 0.000.